PERENCANAAN ALTERNATIF PONDASI KONSTRUKSI SARANG LABA-LABA PADA PALU GRAND MALL - Magfira, Dwi; B., Arifin; Rahayu, Astri (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2014)
Palu Grand Mall located at Diponegoro street, West Palu districts, PERENCANAAN ALTERNATIF PONDASI KCentral Sulawesi using foundation Konstruksi Sarang Laba-Laba( KSLL ). TheKonstruksi Sarang Laba-Laba is a combination of continuous flat concrete slab foundation system with a soil improvement system. This system is specifically utilizes the ground as part of the foundation structure. The purpose of thisresearchare to redesign KSLL foundation that is qualified for qgross â‰¤ qijin.Parameters that used are sondir test results, borlog, as well as laboratory testing such as bulk density and coefficient of consolidation (Cv). The analysis begins with the soil classification, load analysis using SAP. Then calculate the bearing capacity of the foundation, the maximum soil stress,Â  potential settlement, equivalent thickness, KSLLreinforcement dimensions, and RAB in Palu Grand Mall.Based onCPT test results on the location it was obtained that the soil classification is clay for soil at the depth of 0-12 m, clayey silt for soil at the depth 12-15 m and gravelly sand at a depth of 15-20 m. The results obtained from SAP is 356.80 ton for the maximum load. For one segment with a size of 8 mx 8 m the foundation bearing capacity was 335.54 ton/ mÂ². Calculation of the area of load distribution which is reviewed each segment was 11.599mÂ² for construction rib and 11.034 mÂ² for ribsettlement. Control of qgros and qall are met, which a rib construction is qgros 30.762 t/mÂ² <qall335.545 t/mÂ² and rib settlement qgros 32.337 t/mÂ² <qall335.545 t/mÂ². From the calculation it was obtained thatthe maximum soil stress are 3,613 t/mÂ², the potential settlement 4,256 cm for a period of 12 years. Equivalent thickness of rib construction is 125 cm and 170 cm for rib settlement. The reinforcement in the rib construction and rib settlement are using the size of Ã˜10-15 cm (As = 471 mmÂ²) on the condition Ïmin< Ï < Ïmax. The budget plan calculation results showed that for earthwork the budget is Rp. 13,948,320 and Rp. 130.620.019,77 for KSLL foundation work per segment Keywords: bearing capacity, settlement, foundations, konstruksi sarang laba-laba